Avian pallial circuits and cognition: A comparison to mammals. (December 2021) - Güntürkün, Onur; von Eugen, Kaya; Packheiser, Julian; Pusch, Roland
Abstract: Cognitive functions are similar in birds and mammals. So, are therefore pallial cellular circuits and neuronal computations also alike? In search of answers, we move in from bird's pallial connectomes, to cortex-like sensory canonical circuits and connections, to forebrain micro-circuitries and finally to the avian "prefrontal" area. This voyage from macro- to micro-scale networks and areas reveals that both birds and mammals evolved similar neural and computational properties in either convergent or parallel manner, based upon circuitries inherited from common ancestry. Thus, these two vertebrate classes evolved separately within 315 million years with highly similar pallial architectures that produce comparable cognitive functions. Graphical abstract: Image 1 Highlights: Birds and mammals have similar neural circuitries at macro-, meso-, and micro-scale level. These properties evolved in parallel, based upon primitive ancient core circuits. These parallel architectures result in comparable cognitive computations. Degrees of freedom for a neural design for complex cognition seem to be limited.